A diverse panel of hepatitis C virus glycoproteins for use in vaccine research reveals extremes of monoclonal antibody neutralization resistance - Urbanowicz, Richard A.; McClure, Patrick; Brown, Richard J.P.; Tsoleridis, Theocharis; Persson, Mats A.A.; Krey, Thomas; Irving, William L.; Ball, Jonathan K.; Tarr, Alexander W. (American Society for Microbiology, 2016)
Despite significant advances in the treatment of hepatitis C virus (HCV) infection, the need to develop preventative vaccines remains. Identification of the best vaccine candidates and evaluation of their performance in preclinical and clinical development will require appropriate neutralization assays utilizing diverse HCV isolates. We aimed to generate and characterize a panel of HCVE1E2 glycoproteins suitable for subsequent use in vaccine and therapeutic antibody testing. Full-length E1E2 clones were PCR amplified from patient- derived serum samples, cloned into an expression vector, and used to generate viral pseudoparticles (HCVpp). In addition, some of these clones were used to generate cell culture infectious (HCVcc) clones. The infectivity and neutralization sensitivity of these viruses were then determined. Bioinformatic and HCVpp infectivity screening of approximately 900 E1E2 clones resulted in the assembly of a panel of 78 functional E1E2 proteins representing distinct HCV genotypes and different stages of infection. These HCV glycoproteins differed markedly in their sensitivity to neutralizing antibodies. We used this panel to predict antibody efficacy against circulating HCV strains, highlighting the likely reason why some monoclonal antibodies failed in previous clinical trials. This study provides the first objective categorization of cross-genotype patient-derived HCVE1E2 clones according to their sensitivity to antibody neutralization. It has shown that HCV isolates have clearly distinguishable neutralization-sensitive, -resistant, or -intermediate phenotypes, which are independent of genotype. The panel provides a systematic means for characterization of the neutralizing response elicited by candidate vaccines and for defining the therapeutic potential of monoclonal antibodies.